2017
DOI: 10.1097/bsd.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique for Decompression of Severe Thoracic Myelopathy due to Tuberous Ossification of Ligamentum Flavum

Abstract: Segmental en bloc resection of the posterior wall of the thoracic canal is a safe and effective alternative for OLF-related severe thoracic myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Instability can subsequently result in progressive kyphotic deformity and associated neurological deterioration, local recurrence of OLF, or development of OLF at adjacent proximal levels. 13,14,32 Concurrent posterior instrumentation and fusion has been proposed as a strategy to prevent progression of thoracic kyphosis from surgical decompression, although this remains controversial. 11,32 However, two studies in this meta-analysis specifically proposed that good clinical results can be achieved with decompression alone without fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instability can subsequently result in progressive kyphotic deformity and associated neurological deterioration, local recurrence of OLF, or development of OLF at adjacent proximal levels. 13,14,32 Concurrent posterior instrumentation and fusion has been proposed as a strategy to prevent progression of thoracic kyphosis from surgical decompression, although this remains controversial. 11,32 However, two studies in this meta-analysis specifically proposed that good clinical results can be achieved with decompression alone without fusion.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,32 Concurrent posterior instrumentation and fusion has been proposed as a strategy to prevent progression of thoracic kyphosis from surgical decompression, although this remains controversial. 11,32 However, two studies in this meta-analysis specifically proposed that good clinical results can be achieved with decompression alone without fusion. 1,23 The late-onset complication of thoracic kyphosis was not reported in these two studies at a follow-up period of 17.3 and 53.2 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior full‐lamina or semi‐lamina decompression is the traditional operative method for the treatment of OLF. Multiple studies have demonstrated that thoracic vertebra wall excision is the safest and most effective operative method to cure thoracic vertebra OLF. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that thoracic vertebra wall excision is the safest and most effective operative method to cure thoracic vertebra OLF. Wang et al . used the en bloc surgical method centrum posterior column to cure 18 OLF patients.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, the ossification of the dura mater with the OLF makes surgery more difficult. Hence, several surgical decompression procedures including en-bloc laminectomy (8,21), laminoplasty (19), and foraminotomy (15) have been recommended. The outcomes of te surgical treatment are not always satisfactory, and the possibility of neurological deterioration remains a major concern.…”
Section: █ Introductionmentioning
confidence: 99%